POTENSI SUKUK SEBAGAI ALTERNATIF PEMBIAYAAN PEMBANGUNAN DI BANTEN - Zaini Ibrahim (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2013)
Funds of district development sourced from district of earning and budgeting (APBD) constrained when source of revenue rely on district revenue (PAD) as like as taxes. An act penetration innovatory solution is needed to solve the budget deficit problem such as the potency of Sharia bonds (Sukuk). This article discusses what kinds of potency that become strengths and weaknesses then how opportunities and challenges are faced by Banten Province in an effort to take advantage of sukuk as the source of development budgeting in Banten. Furthermore, what strategis are effective to apply in an attempt to make sukuk as the source of development budgeting in Banten. An analysis of classical SWOT (SWOT Analysis-K) used to solve the problem above. First step of SWOT-K analysis is identifying the internal and external factors faced by the Banten province to take advantage of sukuk as a source of development budgeting in Banten. Second is making combination of internal and external factors. Final step is formulating appropriate strategies to be sukuk as an alternative of development funding in Banten. Result of SWOT-K anafysis in Banten Province has the power of aspects of economic resources as basic capital to make use of sukuk for regional development budgeting. Whereas there are two weakness become obstacles, there are human resources and government management. Besides, the market opportunity to make use of sukuk is widely open because Banten Province is one of the provinces that have a positive economic growth. Opportunities become greater with decentralization right in district financial management, but faced challenges are none of juridis basis for the implementation of district sukuk. The existence of UU SBSN does not yet give potency for district to take advantage of sukuk as APBD because the utilization of new sukuk is allowed for APBN. Priority strategic is improving the quality of human resources in field of Sharia finance by increasing professionalism and accountability in management. Improvement of the quality of human resources is accompanied by efforts to encourage the central government and the legislature to revise the constitution of governing district finances in order that accommpodate the source of society loans as instrument of district Sharia bonds (sukuk). Keywords: Budgeting, Bonds, Sukuk, Banten, APBD.